BAURAN PEMASARAN KERAJINAN CENDERAMATA BERBAHAN BAKU BAMBU BATIK (Studi Kasus Pada UD. Betris di Kelurahan Meras Kecamatan Bunaken Kota Manado) - Gita Syahfitri Labatjo; Agnes E. Loho; Lyndon R. J. Pangemanan (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the marketing mix on UD.Betris. The research was conducted in November 2017 until January of 2018. The research method used is case study. Data used in this research are primary data and secondary data. The method of data analysis used is descriptive analysis that describes the implementation of marketing mix of Bamboo Batik Handicraft in Meras Village, Bunakaen Sub-district, Manado City. The result of the research concludes that marketing mix in general have good application in UD. Betris. Based on four aspects, only one aspect is a place that is not well implemented in UD. Betris because the place is not strategic yet.